Growth impairment in children with atrophic autoimmune thyroiditis and pituitary hyperplasia - Domenico Corica; Tiziana Abbate; Anna Malgorzata Kucharska; Malgorzata Wojcik; Francesco Vierucci; Mariella Valenzise; Alessandra Li Pomi; Giorgia Pepe; Gerdi Tuli; Beata Pyrzak; Tommaso Aversa; Malgorzata Wasniewska (BMC, 2024)
Abstract Background Atrophic autoimmune thyroiditis (AAT) is a rare phenotype of autoimmune thyroiditis (AT) in pediatric age. AAT occurs without thyroid enlargement leading to a delay in its diagnosis. Growth impairment is infrequent in autoimmune thyroiditis, if timely diagnosed. Prolonged severe hypothyroidism is a rare cause of pituitary hyperplasia (PH) in childhood. Loss of thyroxine negative feedback causes a TRH-dependent hyperplasia of pituitary thyrotroph cells resulting in adenohypophysis enlargement. A transdifferentiation of pituitary somatotroph cells into thyrotroph cells could explain growth failure in those patients. Methods Twelve patients were retrospectively evaluated at five Italian and Polish Centres of Pediatric Endocrinology for height growth impairment. In all Centres, patients underwent routine clinical, biochemical and radiological evaluations. Results At the time of first assessment, the 75% of patients presented height growth arrest, while the remaining ones showed growth impairment. The study of thyroid function documented a condition of hypothyroidism, due to AT, in the entire cohort, although all patients had no thyroid enlargement. Thyroid ultrasound showed frankly atrophic or normal gland without goiter. Cerebral MRI documented symmetrical enlargement of the adenohypophysis in all patients and a homogeneous enhancement of the gland after the administration of Gadolinium-DPTA. Replacement therapy with levothyroxine was started and patients underwent close follow-up every 3 months. During the 12 months of follow-up, an improvement in terms of height growth has been observed in 88% of patients who continued the follow-up. Laboratory findings showed normalization of thyroid function and the control brain MRI documented complete regression of PH to a volume within the normal range for age and sex. Conclusions This is the largest pediatric cohort with severe autoimmune primary hypothyroidism without goiter, but with pituitary hyperplasia in which significant growth impairment was the most evident presenting sign. AAT phenotype might be correlated with this specific clinical presentation. In youths with growth impairment, hypothyroidism should always be excluded even in the absence of clear clinical signs of dysthyroidism.